A road map for molecular ecology. Issue 10 (24th April 2013) - Andrew, Rose L.; Bernatchez, Louis; Bonin, Aurélie; Buerkle, C. Alex.; Carstens, Bryan C.; Emerson, Brent C.; Garant, Dany; Giraud, Tatiana; Kane, Nolan C.; Rogers, Sean M.; Slate, Jon; Smith, Harry; et al.
Abstract The discipline of molecular ecology has undergone enormous changes since the journal bearing its name was launched approximately two decades ago. The field has seen great strides in analytical methods development, made groundbreaking discoveries and experienced a revolution in genotyping technology. Here, we provide brief perspectives on the main subdisciplines of molecular ecology, describe key questions and goals, discuss common challenges, predict future research directions and suggest research priorities for the next 20 years.